Motywy antyczne we współczesnej dystopii, czyli co wspólnego ze starożytnością ma idea państwa przedstawiona w I części trylogii Igrzyska śmierci Suzanne Collins1 - Gryksa, Edyta (Colloquia Litteraria, 2023)
The aim of the article is to prove that Suzanne Collins was inspired by characters, events and ancient traditions while preparing the first part of the Hunger Games trilogy. The main emphasis was placed on associating the characters with their ancient etymological prototypes, issues related to gladiatorial games, mythological themes and the motifs of war and rebellion.